Jan Svankmajer - Johnson, Keith Leslie, 1974- (Book collections on Project MUSE., 2017)
This synoptic study of Czech filmmaker Jan Svankmajer (b. 1934) presents his career in terms of a Surrealist outlook informed by an idiosyncratic animism.